Experimental Evaluation of Crack Evolution in Rails Using a Phased Array - Whetstone, G.; Liu, T.; Fudlailah, P.; Droddy, C. V.; Allen, D. H. (Journal of nondestructive evaluation, 2023)
Considering the background of civilian and personnel safety as well as supply chain reliability, it is necessary to develop complex rail testing protocols that are capable of validating crack growth rate models, thereby increasing the safety, reliability, and efficiency of railway operations. The objective of the research herein is to consider a common approach to rail testing, which involves the non-destructive evaluation of internal rail cracks using phased array ultrasonic testing (PAUT). This paper focuses on our efforts to utilize PAUT methodology to nondestructively measure internal crack geometry during long term multiaxial cyclic loading of rails with growing internal cracks. Our methods include the employment of a hydraulically powered apparatus that is capable of simultaneously applying both constant axial load and dynamic bending moment to the irregular geometry of a rail head. Then tracking progressive crack growth using a PAUT system in addition to the algorithm developed herein. In this paper we present an overview of our experimental results to date as well as our efforts to improve this critical testing methodology for assessing crack growth rates in rails subject to cyclic loading. Our efforts have in some cases resulted in anomalous measurements of crack geometry, thereby impacting the accuracy of the results in these complex experiments. The results to date suggest the conclusion that additional systems need be implemented in order to standardize the readings in this complex loading environment, including standardization of the initiation point, couplant uniformity, and matching the irregular curvature of the rail head itself.